Potential Regulatory Functions of Propolis to Ameliorate Hematopoietic Disorder in Diabetic Mouse Model - Muhaimin Rifa’i (Journal of Global Pharma Technology, 2017)
Diabetes mellitus (DM) in autoimmune case, related to cytotoxic T cells activation as a response to autoantigen. In the recent studies, propolis is known as a potential immunomodulator. The aim of this study is to determine the effect of propolis as a regulator to ameliorate diabetic mouse model. In vivo experiment was done using streptozotocin-induced diabetic mice. There are five experiment groups; that are DM group (diabetic mice model without treatment); propolis ethanolic extract treatment group doses of 50, 100, and 200 mg/kg BW; and normal mice group. Effect of propolis was observed 14 days post treatment by flow cytometric analysis. The number of CD8+CD62L-, CD4+CD25+CD62L+(Treg), B220+, and NK+ cells was assessed from splenic cells. The result showed that administration of propolis for 14 days could reduce the number of cytotoxic T lymphocytes (CTL) memory significantly (p ≤ 0, 05). Especially the doses of 100 and 200 mg/kg BW could suppress the activation of CTL quite similar to those normal groups. Propolis with the dose of 200 mg/kg BW increase the number of Treg, B220, and NK cells. The increase of Treg may reduce the activation of CTL and prevent tissue damage by autoreactive cells, and finally hematopoietic imbalance can be overcome. Keywords: B220, diabetes mellitus, immunomodulatory, NK, propolis.